Strategi Peningkatan Penerimaan Daerah Melalui Pendapatan Asli Daerah Dari Retribusi Di Kota Manado.. - Lumi, Mario M; rumapea, patar (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: This study aimed to: (1). Knowing the condition of acceptance of Manado City area primarily sourced from levy sources of revenue. (2) Determine strategy to increase revenue from the levy in the city of Manado. The methodology used in this study is a qualitative method in which the research method was used to examine the condition of natural objects (as his opponent is an experiment) where the researcher is a key instrument, conducted the data collection techniques triangulation (combined) and data analysis is inductive. The results showed revenue is a real contribution given by the local community to support the autonomous status granted to the area. Improved performance of Original Region Revenue through a levy can be done by improving the administration of local revenues, as well as through regulatory reform local taxation and levies. Levies in the city of Manado has undergone significant improvement by increasing the number and activity of domestic activities. Suggestions that may be filed as follows: in order to prioritize efforts to increase revenue by evaluating and improving systems that have been implemented, because it still has considerable prospects and potential and Inviting community participation so as to help provide a source of information material in order to periodically evaluate the level of development in general revenue levy, particularly regarding pay resources and increase public service efficiency Key Words: Strategy For Regional Increase Acceptance, Original Region Revenue